2021
DOI: 10.1186/s13046-021-01878-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer-associated fibroblasts promote the survival of irradiated nasopharyngeal carcinoma cells via the NF-κB pathway

Abstract: Background Irradiation has emerged as a valid tool for nasopharyngeal carcinoma (NPC) in situ treatment; however, NPC derived from tissues treated with irradiation is a main cause cancer-related death. The purpose of this study is to uncover the underlying mechanism regarding tumor growth after irradiation and provided potential therapeutic strategy. Methods Fibroblasts were extracted from fresh NPC tissue and normal nasopharyngeal mucosa. Immunohi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 55 publications
(41 reference statements)
1
26
0
Order By: Relevance
“…Significantly, up-regulated genes in tumorderived fibroblasts were enriched in IFN response-related pathways (23). Meanwhile, fibroblasts are also considered as one of the vital factors maintaining the differentiation status of NPC cells because they are frequently associated with the epithelial-tomesenchymal transition (13,126). Targeting infiltrating fibroblasts might also result in decreasing the cancer stem cell pools in NPC to alleviate therapeutic resistance commonly possessed by high stemness cells (126).…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, up-regulated genes in tumorderived fibroblasts were enriched in IFN response-related pathways (23). Meanwhile, fibroblasts are also considered as one of the vital factors maintaining the differentiation status of NPC cells because they are frequently associated with the epithelial-tomesenchymal transition (13,126). Targeting infiltrating fibroblasts might also result in decreasing the cancer stem cell pools in NPC to alleviate therapeutic resistance commonly possessed by high stemness cells (126).…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
“…Meanwhile, fibroblasts are also considered as one of the vital factors maintaining the differentiation status of NPC cells because they are frequently associated with the epithelial-tomesenchymal transition (13,126). Targeting infiltrating fibroblasts might also result in decreasing the cancer stem cell pools in NPC to alleviate therapeutic resistance commonly possessed by high stemness cells (126). CD248 has been found dynamically expressed by cancer-associated fibroblasts (CAFs), and lowly expressed by other stromal cells (127).…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
“…CAF may also protect cancer cells from radiation. Huang et al [ 74 ] found that radioresistant nasopharyngeal carcinoma had a higher infiltration of CAF compared with radiosensitive tissue, and showed that this radioprotective effect was modulated via IL-8/NF-κB signalling. This effect was diminished following treatment with Tranilast – a drug known to inhibit fibrosis and TGF-β signalling.…”
Section: Caf Radiotherapy and Chemotherapymentioning
confidence: 99%
“…Here, the tumor growth delay by inhibiting NF-kB activation was examined in a xenograft model [47,48]. PDX models can reenact the tumor microenvironment; in these models, activation of NF-κB is considered to have an important role in tissue growth.…”
Section: Discussionmentioning
confidence: 99%